2013
DOI: 10.1039/c3cc45924a
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure carbon dioxide uptake for porous organic cages: comparison of spectroscopic and manometric measurement techniques

Abstract: A chemoselective spectroscopic method for measuring CO2 sorption isotherms at pressures up to 14 MPa (140 bar) is validated against manometric measurements and molecular simulations, giving insights into the preferred sorption sites in various crystalline porous organic cages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 17 publications
2
34
0
2
Order By: Relevance
“… Furthermore, CC3‐R is capable of separating F 2 , Cl 2 , and Br 2 molecules by a stepwise temperature program because of the marked differences between their desorption behaviors. One of the other advantages of CC3‐R is that atoms or molecules of air does not interfere with adsorption of halogen gases; the earlier simulation studies have shown that CC3‐R captures N 2 , O 2 , H 2 O, CO 2 , CH 4 , and noble gases at low temperatures . The results of experiments confirm that all O 2 , N 2 , CO 2 , Kr, and Xe gases are passed through a column containing CC3‐R with maximum retention time of 65 min .…”
Section: Discussionmentioning
confidence: 68%
“… Furthermore, CC3‐R is capable of separating F 2 , Cl 2 , and Br 2 molecules by a stepwise temperature program because of the marked differences between their desorption behaviors. One of the other advantages of CC3‐R is that atoms or molecules of air does not interfere with adsorption of halogen gases; the earlier simulation studies have shown that CC3‐R captures N 2 , O 2 , H 2 O, CO 2 , CH 4 , and noble gases at low temperatures . The results of experiments confirm that all O 2 , N 2 , CO 2 , Kr, and Xe gases are passed through a column containing CC3‐R with maximum retention time of 65 min .…”
Section: Discussionmentioning
confidence: 68%
“…We previously investigated whether the internal cavities of the CC2 cages are accessible to gases, or if diffusion is restricted to the 1-dimensional channel running between the cages. 8,29 These results suggest that the accessibility of the cage cavities to nitrogen is dependent on the chirality of the structure: that is, open in the case of the racemic CC2 crystals but closed in the homochiral form.…”
Section: Chiral Cc2 Separated By Co-crystallisationmentioning
confidence: 81%
“…Isostrukturelle Reihen von Käfigen liefern tiefere Einblicke in Struktur-Porositäts-Beziehungen. [108,299,300] Sowohl COFs als auch Käfige haben sich mittlerweile als permanent porçse Materialien etabliert, und auf den ersten Blick gibt es keine offensichtliche Präferenz füre ine der beiden Materialklassen. [138] In geordneten Phasen sind jedoch grçßere Unterschiede zu beobachten, die auf einen signifikanten Beitrag von extrinsischer Porositäti nfolge des unterschiedlichen Packungsverhaltens im Kristall schließen lassen.…”
Section: Porositätu Nd Gasspeicherungunclassified
“…In einigen Fällen wurde auch über die selektive CO 2 -Aufnahme von organischen Käfigen berichtet. [108,299,300] Sowohl COFs als auch Käfige haben sich mittlerweile als permanent porçse Materialien etabliert, und auf den ersten Blick gibt es keine offensichtliche Präferenz füre ine der beiden Materialklassen. Vielmehr sollte die Auswahl im Hinblick auf die gewünschte Anwendung oder andere Parameter wie einfache Prozessierbarkeit oder Stabilitätu nter den Betriebsbedingungen getroffen werden.…”
Section: Angewandte Chemieunclassified